The Role of High Carbon Additives on Physical–Mechanical Characteristics and Microstructure of Cement-Based Composites - Jaroslav Pokorný; Radek Ševčík; Lucie Zárybnická; Luboš Podolka (Buildings, 2023)
Traditional supplementary cementitious materials (SCMs) have been proven to reduce the negative impact of Portland cement production on the environment. However, the availability of SCMs becomes limited due to their extensive usage. For this reason, our work aimed to investigate the effect of partial substitution of ordinary Portland cement (OPC) with two different types of carbon-rich waste powders—biochar (BC) and coal dust (CD), dosed separately up to 10 wt.% of OPC, on the physical, microstructural and mechanical properties of hardened specimens. Obtained data pointed out that replacing OPC with small amounts of BC and CD (not exceeding 5.0 wt.% and 2.5% wt.%, respectively) initiated an increment in mechanical strengths due to a decrease in total open porosity and enhanced formation of hydration products of such composites compared with the reference. Overall, both examined alternatives, if added in appropriate amounts, have the perspective to be effectively applied in cement manufacturing and concrete production, and thus to importantly contribute to the long-term sustainability of the construction industry in view of energy savings, reduced releasing of the greenhouse gasses and mitigating of global climate changes.